KAJIAN PROPORSI TEPUNG JAGUNG (Zea mays) DAN TEPUNG JANTUNG PISANG (Musa paradisiaca L.) DENGAN PENAMBAHAN KUNING TELUR PADA BISKUIT JAGUNG - Enny Karti Basuki Susiloningsih; Fesdila Putri Nurani; Aprilia Tri Sintadewi (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Recently the development of innovation in food products increased in order to add health benefits to those who consume it. Corn flour has a main component of starch about 70% and banana bud flour contains fiber which is high enough to be used as biscuit-making material. The addition of egg yolks in the manufacture of biscuits is used to help improve the texture to be more crispy. This study aims to determine the proportion of corn flour and banana bud flour with the addition of egg yolks to product corn biscuits which is favored by panelists. This study used a completely randomized design (CRD) factorial pattern with two factors. The first factor is the proportion of corn and banana bud flour (90:10, 85:15, 80:20), the second factor is the addition of egg yolk 10%, 20%, 30% (b / b). The best treatment is the proportion of corn flour: banana bud flour = 85: 15 and egg yolk addition of 10% (b / b) with a color preference value of 3.24, taste of 3.40 and aroma of 3.40, yield of 92.25%, content water 3.03%, ash content 1.1%, fat content 10.11%, protein content 9.67%, carbohydrate content 71.04%, crude fiber 3.31%, breaking power1.50 N